Le rôle homosexuel [1968] - Mary McIntosh (Genre, Sexualité et Société)
The current conceptualization of homosexuality as a condition is a false one, resulting from ethnocentric bias. Homosexuality should be seen rather as a social role. Anthropological evidence shows that the role does not exist in all societies, and where it does it is not always the same as in modern western societies. Historical evidence shows that the role did not emerge in England until towards the end of the seventeenth century. Evidence from the « Kinsey Reports » shows that, in spite of the existence of the role in our society, much homosexual behavior occurs outside the recognized role and the polarization between the heterosexual man and the homosexual man is far from complete.